ENHANCING LANGUAGE TEACHING: A MULTIFACETED APPROACH - Muhamadavas Tursunovich Irisqulov; Nargiza Ergashbayevna Yuldasheva (Galaxy International Interdisciplinary Research Journal, 2024)
Effective language teaching requires a diverse array of methods to engage learners and facilitate comprehension. This article explores various teaching strategies, including teacher talk, questioning, note-taking, and game-based activities, highlighting their advantages and disadvantages. Drawing from insights by educational theorist Geoff Petty, the article emphasizes the need for a balanced approach that incorporates both teacher-centered and student-centered methods. Furthermore, it underscores the importance of understanding linguistic levels and instructional strategies to support language learners in achieving their objectives. By adopting a multifaceted approach to language teaching, educators can create stimulating and enjoyable learning environments conducive to linguistic proficiency and fluency.